O espaço dos homens plenos: experiência comparada na educação do campo entre brasil e cuba e as possibilidades de formação omnilateral - Villela, Fabio Fernandes [UNESP] (My University, 2012)
This text aims to present the challenges and opportunities of omnilateral formation as elaborated in Villela (2009-2010). This work has the horizon systematize the educational practices originating from the educational experience of Brasil and Cuba. In the struggle for emancipation, these countries have built and are building unique educational practices. In this sense, we start questioning the historical and theoretical topic, omnilateral formation, and deployment, we discuss school and omnilateral formation. We question specifically issues relating to intellectual and educational organization working in the field schools in Cuba (1960-1975). The issue of intellectual and organizational culture, in a Gramscian perspective (Gramsci, 2000), was addressed in several papers throughout our academic career (Villela, 2003, 2008, 2009). In order to further these issues, we address the challenges of formation for children and rural youth in Latin America. By analyzing the educational practices in the education field, emerges the theme of contemporary global justice.

Este texto tem por objetivo apresentar os desafios e as possibilidades da formação omnilateral conforme elaborado em Villela (2009- 2010). Este trabalho tem por horizonte sistematizar as práticas educativas na educação do campo originadas da experiência educacional no Brasil e em Cuba. No processo de luta pela emancipação, esses países construíram e estão construindo práticas educativas originais. Nesse sentido, partimos da problematização histórico-teórico do tema, formação omnilateral, e por desdobramento, abordamos a escola e as possibilidades de forma- ção omnilateral. Problematizamos especificamente as questões relativas aos intelectuais e a organização trabalho pedagógico nas escolas no campo em Cuba (1960-1975). A questão dos intelectuais e a organização da cultura, sob uma perspectiva gramsciana (Gramsci, 2000), foi abordada em diversos trabalhos ao longo de nossa trajetória acadêmica (Villela, 2003; 2008; 2009). No sentido de aprofundar tais questões, abordamos os desafios da formação de crianças e jovens do campo no Brasil. Ao analisarmos as práticas educativas em educação do campo, emerge a temática contemporânea da justiça global.
The space of multidimensional men: comparative experience in rural education between brazil and cuba and the possibilities of omnilateral formation
Keywords: Práticas Educativas; Educação do Campo; Formação Omnilateral; América Latina; Justiça Global; Educational Practices; Rural Education; Omnilateral Formation; Latin America; Global Justice